DISPENSASI KAWIN DI DESA KARANGJATI KECAMATAN SAMPANG KABUPATEN CILACAP (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this Community Service is to assist the government in socializing the law and increasing public knowledge of the law, especially regarding the Marriage Dispensation in Karangjati Village, Cilacap District. In carrying out Community Service activities which raise the topic "Marriage Dispensation" in Karangjati Village, Sampang District, Cilacap Regency, the Community Service team, Faculty of Law, Wijayakusuma University, Purwokerto, offers solutions in the form of consultation and assistance for the community who will carry out activities related to understanding marriage, purpose of marriage, principles of marriage, conditions of marriage, definition of underage marriage, dispensation for marriage, conditions for dispensation for marriage. This consultation and assistance is attempted to be carried out in a planned and sustainable manner by involving academics who specialize in this topic, village officials, community leaders and youth leaders in Karangjati Village, Sampang District, Cilacap Regency. This community service received a positive response from community members. Before legal counseling is carried out, the counseling participants are first given a pretest and at the end of the counseling a posttest is given. Conclusion: Before legal counseling was carried out, many people did not know about the causes and procedures for marriage dispensations, but after legal counseling was carried out regarding marriage dispensations, people knew and understood about marriage dispensations and procedures, as well as the consequences of marriages under the age of consent. The people of Karangjati village, Sampang District, Cilacap Regency want further legal education to increase legal knowledge and awareness for the people of Karangjati village